Factors Influencing Intention to Use SPayLater in Indonesia - Rezki Orientani; Masmira Kurniawati (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
Payment instruments are part of technological developments. The existence of this development is utilized by finance companies such as peer-to-peer lending technology. Peer-to-peer lending in Indonesia continues to increase, one of the products of peer-to-peer lending companies is SPayLater which is a product of Shopee Indonesia and PT. Lentera Dana. This study provides an overview of the effect of perceived ease of use, perceived usefulness, perceived compatibility towards attitude toward using and perceived cost, subjective norm, personal innovativeness on intention to use. This study uses a quantitative method by distributing 250 online questionnaires to Shopee consumers. Data analysis was carried out using SEM and assisted by PLS 3 software. The results of this study indicate that perceived ease of use does not affect attitude toward using SPayLater payment system, perceived cost and personal innovativeness do not affect intention to use the SPayLater payment system, while perceived usefulness, perceived compatibility, attitude toward using and subjective norm affect the intention to use the SPayLater payment system.